ECUMENISM: TOWARDS AN 'EXCHANGE OF GIFTS' - Farrell, Marie T (Compass (Kensington, N.S.W.), 2014)
Baptism is thus ordained toward a complete profession of Christ, a complete incorporation into the system of salvation such as Christ himself willed it to be, and finally through a complete integration into Eucharistic communion.6 When misunderstood, principles governing the practice of'reciprocal Eucharist' in the Catholic Church frequently cause concern and indignation.\n As Pope Francis teaches, the Catholic Church can contribute to being a 'leaven of peace' in a war-ravaged world alongside and with trust in all Christian pilgrims.19 In seeking ecumenical unity, the Anglican Church can offer the 'gift' of its fourfold patrimony: of exercising a synodal character of governance as a corporate and conciliar system of decision-making and authority; of its distinctive spiritual tradition liked to pastoral practice including the re-establishment of religious life and the valuable gifts of evangelical and reformed piety; of the theological traditions of the Caroline Divines and the Tractarian movement as well as the contribution of 'Broad Church' thinkers who have shaped Anglican identity; and of its liturgical and musical tradition of worship in English over many centuries.20 At the heart of the gift of Methodism are the gifts of John and Charles Wesley-their evangelical zeal to reform the inner life of the Church, their pursuit of personal holiness, care for the poor and their enduring hymns. Methodist-Catholic dialogue has indicated that, although the 'spiritual empowerment of lay people for ministry and mission' is for them a 'gift' of the Spirit derived from baptism, they may, in the future, come to recognise the value the Petrine ministry of the Bishop of Rome as a final decision-making authority in the Church.21 In Australia, precious 'gifts' received from Orthodox tradition and preserved within Eastern Rite Catholic communities are significant for the ecclesial life of 'Latin' Catholics.